Description and Reference: Language as a Possibility for Veracity. A Matter of World-System Limits and Speech Acts - Giraldo Gutiérrez, Francisco Luis; Londoño Vásquez, David Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article deals with the concept of language, and the way in which, as a manmade artifact, it can be understood as a means of representation and expression, with the pretension of validating the things it does not know -the object- as well as the way to know them. In that way, we draw from the idea of language as a system, a social semiotics and an intention. Through language and the communicative act of interlocution, the subject determines the veracity and validity of a fact. Linguistic action performs in the system and for the system, and establishes the level of agreement between the idea -whether it be thought or made manifest- and the object, as a final product of its ability to act and communicate. Our thesis is that, regardless of the way or ways in which linguistic codes are combined, what really matters is their capacity for veracity. In the same way, these levels and possibilities are limited or amplified by the world-systems in which the speaking subjects are involved.